2004
DOI: 10.1590/s0102-76382004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Seguimento clínico a médio prazo com uso exclusivo de enxertos arteriais na revascularização completa do miocárdio em pacientes com doença coronária triarterial

Abstract: Seguimento clínico a médio prazo com uso exclusivo de enxertos arteriais na revascularização completa do miocárdio em pacientes com doença coronária triarterial Method: Between July 1995 and July 1997, 137 consecutive patients with triple vessel coronary atherosclerotic disease underwent complete coronary artery bypass grafting exclusively using arterial grafts. Of these patients, 112 (81.7%) were male, with ages ranging from 36 to 78 years old (mean 56.5 years). Three hundred and sixty-three arterial grafts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…One of the biggest advances in CABG was the use of the internal thoracic artery (ITA) anastomosed to the left anterior descending branch (AD) of the left coronary artery [2,3], proven in the 80s, as the gold standard in CABG because of its higher patency in the medium and long term compared to the saphenous vein (SV). Consequently, these studies have led surgeons to search for new arterial grafts [4], such as right internal thoracic artery, radial, gastroepiploic [5] and inferior epigastric [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest advances in CABG was the use of the internal thoracic artery (ITA) anastomosed to the left anterior descending branch (AD) of the left coronary artery [2,3], proven in the 80s, as the gold standard in CABG because of its higher patency in the medium and long term compared to the saphenous vein (SV). Consequently, these studies have led surgeons to search for new arterial grafts [4], such as right internal thoracic artery, radial, gastroepiploic [5] and inferior epigastric [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is no increase in the operative time, there is no more bleeding, low output or mortality by its utilization as has already been demonstrated [13,17].…”
Section: Commentsmentioning
confidence: 67%
“…The utilization of the left internal thoracic artery to the anterior intraventricular branch (with all its benefits) has already been proven [5][6][7], including its utilization in over 70-year-old patients. The use of arterial grafts has been the primary goal of all services, trying to reduce the reoperation and cardiovascular event rates [8,9,[11][12][13]. In spite of the great applicability of the saphenous graft, it is known that its evolution over the mid term and long term is unsatisfactory [6,11,14,15].…”
Section: Commentsmentioning
confidence: 99%
“…LYTLE et al [3]. statistically showed that patients undergoing CABG with two mammary arteries instead of one had a longer survival and a longer period free of Redo and/or PTCA [4][5]. Therefore, on the basis of this and other experiences, it was decided to change our technique of coronary revascularization towards the exclusive use of arterial conduits, in order to obtain greater benefits in the long term.…”
Section: Discussionmentioning
confidence: 99%